Analysis of The Work Program of The Wahidiyah Childhood Development Agency in Internalizing Spiritual Intelligence - Rizkan Syahbudin; Giyars Giyars (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: Analysis of The Work Program of The Wahidiyah Childhood Development Agency in Internalizing Spiritual Intelligence Children are the future asset of the country. This is because they are the driving wheels of the nation's economy and education. So that on the mandate of the Prophet so as not to leave the people who are weak, it is necessary to have an institution that makes programs that prioritize children's spiritual intelligence. This needs to be done so that they will have a good mentality in the future. To find out the programs carried out by an educational institution, this research uses qualitative research methods. The objects studied in this study are efforts to improve children's spiritual intelligence to achieve educational goals, analysis of the work program of the North Bengkulu branch of the Wahidiyah Child Development Board (BPKW) based on theoretical studies related to spiritual intelligence and strategies to increase spiritual intelligence. The results of the research show that this institution has created a systematic spiritual intelligence program. Through well-scheduled religious activities.Abstrak: Analisis Program Kerja Badan Pembina Kanak-Kanah Wahidiyah (BPKW) Dalam Internalisasi Kecerdasan Spiritual Anak anak merupakan aset masa depan negara. Hal ini disebabkan merekalah yang akan menjadi roda penggerak ekonomi dan pendidikan bangsa. Sehingga atas amanah Rasulullah agar tidak meninggalkan umat yang lemah, maka perlu lembaga yang membuat program yang mengutamakan kecerdasan spritual anak-anak. Hal ini perlu dilakukan agar mereka kelak akan punya mental yang baik. Untuk mengetahui program program yang dilakukan oleh sebuah badan pendidikan maka penelitian ini menggunakan metode penelitian kualitatif. Objek yang dikaji dalam penelitian ini adalah upaya meningkatkan kecerdasan spiritual anak untuk meraih tujuan pendidikan, analisis program kerja Badan Pembina Kanak-Kanak Wahidiyah (BPKW) cabang Bengkulu Utara berdasarkan kajian-kajian teori berkaitan dengan kecerdasan spiritual dan strategi peningkatan kecerdasan spiritual. Hasil penelitian menunjukkan bahwa lembaga ini sudah membuat program kecerdasan spiritual yang tersistematis. Melalui kegiatan-kegiatan keagaamaan yang sudah terjadwal dengan baik.